2022
DOI: 10.3389/fmed.2021.797479
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Retinal Vasculature in Rhegmatogenous Retinal Detachment Based on Ultra-Widefield Fundus Imaging

Abstract: PurposeTo quantitatively analyze retinal vascular morphological features, such as vascular density, caliber, and tortuosity, in rhegmatogenous retinal detachment (RRD).MethodsA total of 244 patients with RRD and 400 healthy controls (HC) were included. Retinal fundus images were collected using OPTOS PLC Daytona P200T. Retinal images were divided into RRD and non-RRD regions of interest (ROIs). All visible retinal fundus vessels were then extracted mainly based on edge detection within ROI to form the whole-va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The most prevalent form of neurosensory retina separation from the retinal pigment epithelium (RPE) is the rhegmatogenous retinal detachment. This type of detachment disrupts the retinal vasculature leading to smaller vascular diameters, tortuosity, and vascular density ( 195 ). Capillary dilatation, hyperpermeability and fluorescein leakage have also been observed with fluorescein angiography on the detached retina, and have been proposed to originate from tissue hypoxia ( 196 , 197 ).…”
Section: Myopia-associated Conditions Showing Vascular Alterationsmentioning
confidence: 99%
“…The most prevalent form of neurosensory retina separation from the retinal pigment epithelium (RPE) is the rhegmatogenous retinal detachment. This type of detachment disrupts the retinal vasculature leading to smaller vascular diameters, tortuosity, and vascular density ( 195 ). Capillary dilatation, hyperpermeability and fluorescein leakage have also been observed with fluorescein angiography on the detached retina, and have been proposed to originate from tissue hypoxia ( 196 , 197 ).…”
Section: Myopia-associated Conditions Showing Vascular Alterationsmentioning
confidence: 99%
“…Sato et al reported the mean circulation time in detached and undetached areas, demonstrating a slower blood flow in detached ones 29 . Using ultrawide-field imaging and OCTA, Feng described qualitative and quantitative changes in retinal vasculature in both RRD and non-RRD areas 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant progress in the use of UFI for diagnosing and managing ocular diseases, current classification methods still have limitations. Many existing studies focus only on single diseases, such as diabetic retinopathy [ 4 , 5 , 6 , 7 ], glaucoma [ 8 ], or retinal detachment [ 9 , 10 , 11 ]. On the other hand, some studies have made attempts at classifying multiple diseases but limit their data to images containing only a single disease [ 12 , 13 ], making it less practical for real-world applications.…”
Section: Introductionmentioning
confidence: 99%